Impact of Heterozygosity for Acid-Labile Subunit (IGFALS) Gene Mutations on Stature: Results from the International Acid-Labile Subunit Consortium - Fofanova Gambetti, Olga V. (2010)
Context: To date, 16 IGFALS mutations in 21 patients with acid-labile subunit (ALS) deficiency have been reported. The impact of heterozygosity for IGFALS mutations on growth is unknown. Objective: The study evaluates the impact of heterozygous expression of IGFALS mutations on phenotype based on data collected by the International ALS Consortium. Subjects/Methods: Patient information was derived from the IGFALS Registry, which includes patients with IGFALS mutations and family members who were either heterozygous carriers or homozygous wild-type.Within each family, the effect ofIGFALSmutations on stature was analyzed as follows: 1) effect of two mutant alleles (2ALS) vs. wild-type (WT); 2) effect of two mutant alleles vs. one mutant allele (1ALS); and 3) effect of one mutant allele vs. wild-type. The differences in height SD score (HtSDS) were then pooled and evaluated. Results: Mean HtSDS in 2ALS was 2.31 0.87 (less than 2 SDS in 62%); in 1ALS, 0.83 1.34 (less than 2 SDS in 26%); and in WT, 1.02 1.04 (less than 2 SDS in 12.5%). When analyses were performed within individual families and pooled, the difference in mean HtSDS between 2ALS and WT was 1.93 0.79; between 1ALS and WT, 0.90 1.53; and between 2ALS and 1ALS, 1.48 0.83. Conclusions: Heterozygosity for IGFALS mutations results in approximately 1.0 SD height loss in comparison with wild type, whereas homozygosity or compound heterozygosity gives a further loss of 1.0 to 1.5 SD, suggestive of a gene-dose effect. Further studies involving a larger cohort are needed to evaluate the impact of heterozygous IGFALS mutations not only on auxology, but also on other aspects of the GH/IGF system.